Cortisol reactivity to psychosocial stress mediates the relationship between extraversion and unrestricted sociosexuality. (November 2015) - Wilson, M. Claire; Zilioli, Samuele; Ponzi, Davide; Henry, Andrea; Kubicki, Konrad; Nickels, Nora; Maestripieri, Dario
Abstract: We investigated the hypotheses that extraversion is associated with unrestricted sociosexuality (operationalized as greater sexual experience and greater short-term mating orientation) and that this association is mediated by reduced cortisol reactivity to psychosocial stress. Study participants were heterosexual male college students (n = 109). Extraversion was assessed with the Big Five Inventory and sociosexuality was assessed with the Multidimensional Sociosexuality Orientation Inventory. Cortisol reactivity to psychosocial stress was assessed via three saliva samples collected immediately before, immediately after, and 15 min after the Trier Social Stress Test. Extraversion was associated with greater sexual experience but not with greater short-term mating orientation. As predicted, more extraverted individuals showed a lower increase in cortisol in response to psychosocial stress than less extraverted individuals. Previous sexual experience and short-term mating orientation were negatively correlated with cortisol reactivity to stress. Finally, mediation analyses confirmed our hypothesis that cortisol reactivity to psychosocial stress is a mechanism mediating the association between extraversion and unrestricted sociosexuality. These findings have implications for our understanding of the benefits and costs of different personality traits as well as for our understanding of the determinants or correlates of individual differences in sociosexuality. Highlights: Young men's extraversion is associated with greater sexual experience. More extraverted individuals show a lower cortisol response to stress. Unrestricted sociosexuality is negatively correlated with cortisol reactivity to stress. Reactivity to stress mediates the association between extraversion and sociosexuality.